Legal Apptitude and Legal Reasoning for the CLAT - A.P. Bhardwaj (Pearson, 2009)
Legal Aptitude and Legal Reasoning for the CLAT prepares aspirants in the four essentials of legal aptitude that are the basis of the -Legal Aptitude and Reasoning- section of the entrance tests: legal maxims and terms, constitutional law, civil law and criminal law. Encouraging students to reflect upon problems rather than give regurgitated answers, and designed to strengthen general legal reasoning, the book helps to deepen understanding of crucial aspects of legal aptitude such as constitutional awareness, legal situations and issues, and legal decisions and their judicious and discriminate interpretations. The practice problems provided have been used and tested to acclaim by hundreds of the author-s students.
Keywords: Legal Aptitude-- Legal Reasoning